2023
DOI: 10.33549/physiolres.934969
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Nephrectomized SHR/NDmcr-cp Rat Shows a Progressive Decline of Glomerular Filtration With Tubular Interstitial Lesions

Abstract: In patients with diabetic kidney disease (DKD), the estimated glomerular filtration rate (eGFR) or creatinine clearance rate (Ccr) is always used as an index of decline in renal function. However, there are few animal models of DKD that could be used to evaluate renal function based on GFR or Ccr. For this reason, it is desirable to develop animal models to assess renal function, which could also be used for the evaluation of novel therapeutic agents for DKD. Therefore, we aimed to develop such animal model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The result showed that the administration of 33 tended to reduce the plasma creatinine levels compared to vehicle group, suggesting that 33 has renoprotective potential. Therefore, we will conduct a long-term administration in a renal disease model such as the diabetic kidney disease (DKD) model we have reported …”
Section: Resultsmentioning
confidence: 99%
“…The result showed that the administration of 33 tended to reduce the plasma creatinine levels compared to vehicle group, suggesting that 33 has renoprotective potential. Therefore, we will conduct a long-term administration in a renal disease model such as the diabetic kidney disease (DKD) model we have reported …”
Section: Resultsmentioning
confidence: 99%